STUDI KASUS FAKTOR PENYEBAB ARTEFAK PADA RADIOGRAF COMPUTED RADIOGRAPHY DI RS PKU MUHAMMADIYAH SRUWENG - Nurliscyaningsih, Ike Ade; Alfiah, Sofi Huril; Fa’ik, Muhamad; Utami, Asih Puji (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Quality assurance (QA) and quality control (QC) are essential to maintaining the quality of radiology services. Providing optimal healthcare requires professionalism and skillful work. To achieve accurate diagnoses, high-quality radiographic images are necessary, and artifacts are a common issue in computed radiography (CR). At PKU Muhammadiyah Sruweng Hospital, artifacts are frequently observed in CR images, necessitating an investigation into the contributing factors. This research aims to identify the causes of artifacts and determine the percentage of artifacts in CR images at PKU Muhammadiyah Sruweng Hospital. The study design is qualitative and descriptive. Data collection involves direct observation of existing artifact issues. Once the problems are identified, the data is analyzed on the computer based on the factors contributing to the artifacts. The data obtained is further reinforced through interviews. The data range used for the study is from September 2022 to November 2022. The research results indicate that operator errors, issues with the imaging plate, exposure factors, and the use of grids are the primary causes of artifacts in radiology images. The percentage of artifacts during the three-month period averaged 6.7%, exceeding the limit set by KMK 2008. To reduce artifacts, it is recommended to provide training for operators to enhance their skills, ensure proper patient preparation, perform routine maintenance on imaging plates and radiology systems, and pay attention to the appropriate use of grids. Continuous evaluation of radiology image acquisition is also crucial to improving the quality of healthcare services at PKU Muhammadiyah Sruweng Hospital.